The Use of English Songs in Teaching Listening Skills Through Online Learning at Junior High School Level - Yuli Astutik; Khofifah Indah Dia Pangestu (Borneo Educational Journal (Borju), 2022)
This article describes the implementation of English songs in the listening class at junior high school. Moreover, this article explains the implementation of English songs used in listening learning for eighth grade students and the difficulties faced by teachers when teaching English in listening classes at junior high school. The study used a qualitative descriptive method. The subject of the research is the teacher. The methods of data collection were interviews and observation. The result of this study indicates that the teacher in implementing teaching listening used three stages such as Pre-Listening, While Listening, and Posst Listening, and that the difficulties that the teacher had were internal and external factors. The findings show that English teachers are very proficient in implementing English songs in teaching synchronous listening skills through Zoom Cloud Software at the junior high school level, both verbally and nonverbally. However, teachers also experience difficulties both internally, such as students who lack English vocabulary, and externally, such as the difficulty of internet connection, which often occurs. The results of this study imply that it turns out that listening skills learning can be done well online if the teacher understands the meaning of each lyric and has good knowledge of such things as content, pedagogy, and technology.